Tyrosine kinase c-MET as therapeutic target for radiosensitization of head and neck squamous cell carcinomas - Lüttich, Lina; Besso, María José; Heiden, Stephan; Koi, Lydia; Baumann, Michael; Krause, Mechthild; Dubrovska, Anna; Linge, Annett; Kurth, Ina; Peitzsch, Claudia (Cancers, 2021)
The receptor tyrosine kinase c-MET activates intracellular signaling and induces cell proliferation, epithelial-to-mesenchymal-transition and migration. Within the present study, we validated the prognostic value of c-MET in patients with head and neck squamous cell carcinoma (HNSCC) treated with radio(chemo)therapy using the Cancer Genome Atlas database and found an association of increased MET gene expression and protein phosphorylation with reduced disease-specific and progression-free survival. To investigate the role of c-MET-dependent radioresistance, c-MET-positive cells were purified from established HNSCC cell lines and a reduced radiosensitivity and enhanced sphere-forming potential, compared to the c-MET-depleted cell population, was found in two out of four analyzed cell lines pointing to regulatory heterogeneity. We showed that c-MET is dynamically regulated after irradiation in vitro and in vivo. Interestingly, no direct impact of c-MET on DNA damage repair was found. The therapeutic potential of eight c-MET targeting agents in combination with irradiation demonstrated variable response rates in six HNSCC cell lines. Amongst them, crizotinib, foretinib, and Pha665752 exhibited the strongest radiosensitizing effect. Kinase activity profiling showed an association of crizotinib resistance with compensatory PI3K/AKT and MAP kinase signaling. Overall, our results indicate that c-MET is conferring radioresistance in HNSCC through modulation of intracellular kinase signaling and stem-like features.
Gesehen am 10.06.2021